2021
DOI: 10.1302/2633-1462.23.bjo-2020-0155.r1
|View full text |Cite
|
Sign up to set email alerts
|

The dawn of a new competency-based training era

Abstract: The imminent introduction of the new Trauma & Orthopaedic (T&O) curriculum, and the implementation of the Improving Surgical Training initiative, reflect yet another paradigm shift in the recent history of trauma and orthopaedic training. The move to outcome-based training without time constraints is a radical departure from the traditional time-based structure and represents an exciting new training frontier. This paper summarizes the history of T&O training reform, explains the rationale for chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The number of foundation programme doctors pursuing higher training in orthopaedics has steadily declined, with the experience of foundation doctors and medical students having a significant impact on career path after completion of their foundation training. [30][31][32] The reforms to undergraduate orthopaedic training, along with appropriate supplementation at the postgraduate stage, will be vital in enticing graduates into a career in this field to ensure the maintenance of adequate musculoskeletal care provision in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of foundation programme doctors pursuing higher training in orthopaedics has steadily declined, with the experience of foundation doctors and medical students having a significant impact on career path after completion of their foundation training. [30][31][32] The reforms to undergraduate orthopaedic training, along with appropriate supplementation at the postgraduate stage, will be vital in enticing graduates into a career in this field to ensure the maintenance of adequate musculoskeletal care provision in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially, looking forward to how higher orthopaedic training is adapting to reduced working hours and increased training demands, using methods such as simulation may provide useful suggestions for undergraduate teaching. 30 , 31 The current evidence base suggests that interactive, patient- or case-focused, senior-led bedside and small group teaching provides students with the most educational value for the time invested.…”
Section: Discussionmentioning
confidence: 99%
“…FPA is an attractive candidate outcome measure for simulation-based studies where assessment of skill transfer from the laboratory to real-world practice is required. It may also have applicability in the modern competence-based training climate, 3 where the procedure-based assessment (PBA) has recognized limitations. 4,5 Assessment of technical skill in the real-world clinical environment has significant known methodological challenges, a recent large systemic review 1 showed that none of the technical skill assessment tools currently in use in orthopaedic training across the world satisfy the Norcini criteria 6 for effective assessment.…”
Section: Introductionmentioning
confidence: 99%
“…FPA is an attractive candidate outcome measure for simulation-based studies where assessment of skill transfer from the laboratory to real-world practice is required. It may also have applicability in the modern competence-based training climate, 3 where the procedure-based assessment (PBA) has recognized limitations. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…It is a completely different way to think about training. I would recommend all UK-based readers (and those overseas with an interest in training) read the excellent summary from James et al, 1 which sets everything into context.…”
mentioning
confidence: 99%